Physioterapy in a child shelter: An experience report of an extension project - Sin Singer Brugiollo, Alessa; Martins Coelho, Cristina; Palermo Ferreira, Mariana Cristina; Miranda Máltaro, Caroline; Pereira Braga, Sara; Ribeiro dos Santos, Ruth Ellen; de Viveiros Gomes, Daniela; Defilipo, Erica Cesário (Guará Journal, 2018)
Child shelters have often been cited as sites of negative impact on neuromotor development and are important risk factors for acute respiratory infections in this population. In this way, the monitoring of the neuromotor development and the ventilatory function of children living in shelter institutions should be prioritized, with actions to prevent and promote health. The aim of this study is to report the experience of physical therapist undergraduates’ students in a child care institution in the city of Governador Valadares, Minas Gerais. This project consisted in evaluating the motor development and the ventilatory function of infants and children, providing physiotherapeutic care and orientations to caregivers. The experience at the shelter allowed physical therapist undergraduates’ students to inte-grate teaching with practice through physical therapy assessment and treatment in pediatrics, early identification of risk factors related to institutionalization and detection of delays in motor development and respiratory signs and symptoms.